Intertextualidade constitutiva em textos produzidos por alfabetizandos adultos em sala de aula - Rios, Guilherme Veiga (Cadernos de Linguagem e Sociedade, 2010)
This paper discusses a specific practice of text production in a community adult literacy programme. The analysis focuses on the category of ‘constitutive intertextuality’ from Critical Discourse Analysis (Fairclough, 1992; 1995) and is also oriented by the New Literacy Studies (Street, ed., 1993; Street, 1995). Four learners’ texts are analysed and two are contrasted in order to observe voice heterogeneity and the diversity of community resources which learners draw on to write. Finally, we argue in favour of the adoption of a comprehensive view that incorporates these diverse resources in community-oriented adult literacy programmes.